The state dependent impact of bank exposure on sovereign risk - Maximilian Podstawski; Anton Velinov (Journal of Banking & Finance, 2018)
The theoretical literature remains inconclusive on whether changes in bank exposure to the domestic sovereign have an adverse effect on the sovereign risk position through a diabolic loop in the sovereign-bank nexus, or reduce perceived default risk by acting as a disciplinary device for the sovereign. In this paper we empirically analyze the impact of exogenous changes in bank exposure on the risk position of the sovereign within a Markov switching structural vector autoregressive in heteroscedasticity (MSH-SVAR) framework for a set of EMU countries. We add to the methodological literature by allowing for regime dependent shock transmissions according to the volatility state of the financial system. Finding support for both, a stabilizing and a destabilizing effect, we document a clear clustering among the country sample: rising bank exposure increased default risk for the EMU periphery, but decreased credit risk for the core EMU countries during times of financial stress.
Keywords: C32; E44; G10; 330; Markov-switching; Heteroscedasticity; Identification; Sovereign-bank interlinkages; Sovereign risk; Credit default swap; Contagion